Synthesis of New 5′-Norcarbocyclic Aza/Deaza Purine Fleximers - Noncompetitive Inhibitors of E.coli Purine Nucleoside Phosphorylase - Khandazhinskaya, Anastasia; Fateev, Ilja; Konstantinova, Irina; Esipov, Roman; Polyakov, Konstantin; Seley-Radtke, Katherine; Kochetkov, Sergey; Matyugina, Elena (Frontiers in Chemistry, 2022)
A new series of flexible 5’-norcarbocyclic aza/deaza-purine nucleoside analogues were synthesized from 6-oxybicyclo[3.1.0.]hex-2-ene and pyrazole-containing fleximer analogs of heterocyclic bases using the Trost procedure. The compounds were evaluated as potential inhibitors of E.coli purine nucleoside phosphorylase. Analogues 1-3 were found to be noncompetitive inhibitors with inhibition constants of 14-24 mM. From the data obtained, it can be assumed that the new 5'-norcarbocyclic nucleoside analogs interact with the active site of the PNP like natural heterocyclic bases. But the same time the presence of a cyclopentyl moiety with 2’ and 3’ hydroxyls is necessary for the inhibitory properties, since compounds 8-10, without those group did not exhibit an inhibitory effect under the experimental conditions.